A Prospective Evaluation of a 4th Generation Total Ankle Prosthesis with 2-Year Follow-Up. Issue 4 (November 2022) - Gross, Christopher E.; Strasser, Nicholas L.; Vora, Anand M.; Friscia, David A.; Doty, Jesse F.
Category: Ankle Arthritis; Ankle Introduction/Purpose: The availability of fourth-generation ankle replacements has burgeoned over the past several years. These ankle replacements benefit from improved surgical technique, respect for bony preservation, and increased surgeon awareness of operative indications. Documentation of implant survivability and comparison studies of the latest generation implants are limited. The purpose of this study is report on prospectively collected patient reported outcome measures (PROMs) in a multi-institutional study of a fourth-generation total ankle. Methods: Patients presenting for a total ankle replacement at 9 institutions were prospectively enrolled and implanted in both academic and private settings. Each patient received an INFINITY ankle prothesis (Stryker, Memphis, TN, USA) Patients had demographics and PROMs recorded pre-operatively and at 6 month, 12 months, and 24- month intervals. The following PROMs were collected: Ankle Osteoarthritis Score (AOS), PROMIS Global Physical Health, Foot and Ankle Outcome Score (FAOS), and satisfaction scores. The preoperative and latest follow-up scores for patients with two years of follow-up were analyzed. Results: A total of 147 patients were enrolled :(54.7% male) average age of 64.2 +- 9.4 years old, average BMI of 31.0 +- 5.2. pre- operative diagnosis for arthritis type was degenerative arthritis (48.7%), rheumatoid arthritis (2.7), post-traumatic arthritis (47.9%), and other (0.70%). Thirty-seven percent of patients had previously undergone surgery at the index joint. Eighty-eight patients had at least two years of follow-up. There were 3 (1.3%) clinical failures:(2 with aseptic tibial component loosening: at months 17 and 21, and 1 tibial subsidence at month 14). The patients improved in all PROMs domains at two years including: Mean Total AOS (17.2 +- 18.3, p<.0001); PROMIS Global Physical Health (47.6 +- 7.4, p<.0001); Total FAOS (76.3 +- 18.7, p<.0001). 97.5% of patients were satisfied with their surgery. Conclusion: At two-year post-implantation follow-up, the INFINITY total ankle replacement had a low revision rate and proved to be safe and effective compared to historical ankle replacement outcomes. Patients were overwhelmingly satisfied and had statistically significant clinical improvements in each domain of their PROMs.